Tracking key CAADP indicators and implementation [In the 2014 ATOR] - Bahiigwa, Godfrey; Benin, Samuel; Tefera, Wondwosen; Jemaneh, Samson (International Food Policy Research Institute, 2015)
This chapter highlights Africa’s progress on 15 indicators across the three levels of the CAADP Results Framework. Level 1 includes the high-level outcomes and impacts to which agriculture contributes, including wealth creation; food and nutrition security; economic opportunities, poverty alleviation, and shared prosperity; and resilience and sustainability. Level 2 presents the outputs from interventions intended to transform the agriculture sector and achieve inclusive growth: agricultural production and productivity; increased intra-African regional trade and functional markets; expanded local agroindustry and value-chain development, inclusive of women and youth; increased resilience of livelihoods and improved management of risks in agriculture; and improved management of natural resources for sustainable agriculture. Level 3 presents inputs and processes required to strengthen systemic capacity to deliver CAADP results and create an enabling environment for agricultural transformation to take place: effective and inclusive policy processes; effective and accountable institutions, including assessing implementation of policies and commitments; strengthened capacity for evidence-based planning, implementation, and review; improved multisectoral coordination, partnerships,